Bioresorbable tyrosol‐derived poly(ester‐arylate)s with tunable properties. Issue 10 (28th March 2021) - Cohen, Jarrod; Shultz, Robert B.; Mullaghy, Andrew; Gwin, Christine; Kohn, Joachim
Abstract: We designed and developed a novel library of tyrosol‐derived poly(ester‐arylate)s that exhibit tunable chemical, thermal, mechanical, and degradative properties. To build the library, the diphenols 4‐hydroxyphenethyl 2‐(4‐hydroxyphenyl)acetate (HTy) and 4‐hydroxyphenethyl 3‐(4‐hydroxyphenyl)propanoate (DTy) are synthesized and subsequently polymerized with various diacids. Characterization of library members is performed in order to assess the impact of chemical structure on polymer properties. Specifically, the relative influence of diphenol pseudosymmetry versus asymmetry, diacid carbon chain length, and diacid bond rigidity on resulting properties is investigated. Diphenol choice greatly impacts resulting polymer thermal properties and processability. HTy‐containing polymers generally have lower melting temperatures compared to their DTy‐derived counterparts and are easier to quench in the amorphous phase. As a result, processing results in greater tunability for HTy‐derived polymers. One specific example was pHTy3, which increased its tensile modulus from 1 GPa to 3 GPa upon drawing. Diacid lengths and bond rigidity also significantly influence thermal, mechanical, and degradative properties. In all, members of this library can be synthesized efficiently, with high molecular weight and exhibit a wide range of properties, motivating future commercial translation. Abstract :